The Obstacle is the Way - Holiday, Ryan (London Profile Book, 2015)
The Obstacle Is the Way: The Timeless Art of Turning Trials into Triumph is the third book by author Ryan Holiday. It was published in 2014. It is a book which offers individuals a framework to flip obstacles into opportunities, an approach crafted by Holiday. It was inspired by the philosophy of stoicism